Evaluasi Pengaruh Penambahan Limbah HDPE pada Campuran Aspal terhadap Karakteristik Marshall - Amir Akh. Faizal; Prikasari Ester; Wibawanto Hadi Surya (Jurnal Spesialis Teknik Sipil (JSpTS), 2026)
Road infrastructure is one of the key components in supporting mobility and economic growth. However, the quality of road pavement often deteriorates due to high traffic loads and changes in environmental conditions. Therefore, innovative efforts are needed to improve the performance of asphalt mixtures. One approach that can be taken is the use of High Density Polyethylene (HDPE) plastic waste as an additive in asphalt mixtures. This study aims to investigate the effect of adding HDPE waste on the characteristics of AC-WC (Asphalt Concrete – Wearing Course) asphalt mixtures using the Marshall method through dry mixing. The variations in HDPE content used are 0%, 3%, 5%, 7%, and 9% of the asphalt weight. Tests were conducted to obtain Marshall parameters such as stability, flow, Marshall Quotient (MQ), Void in Mix (VIM), Void in Mineral Aggregate (VMA), and Void Filled with Bitumen (VFB). The results of the study indicate that the addition of HDPE waste significantly affects the stiffness and stability of the mixture. At certain concentrations, mixtures containing HDPE can enhance stability and Marshall Quotient values, making the mixture stiffer and more resistant to traffic loads. However, excessive HDPE addition tends to reduce mixture flexibility, as indicated by decreased flow values. The optimal HDPE concentration in this study was found to be around 5%–7%, where the mixture meets Marshall specifications and provides the best performance. The use of HDPE plastic waste in asphalt mixtures not only improves road pavement quality, but also contributes positively to plastic waste management and environmental sustainability.